Ethno Cultural Concept of Family Life in Malaysian Literature in English - Murooj Fareed Majeed (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
A family involves two or more persons who live in the same household and are related through blood, marriage, or adoption . Family is “a social group branded by a common home, economic collaboration, and reproduction. It includes grown-ups of both genders, at least two of whom sustain a socially approved sexual relationship, and one or more children, own or adopted, of the adults living together(Alakavuklar, 2009).The study is going to examine the concept of family in term of father/mother, father /children, mother/children binary opposition between three main ethnic groups in Malaysia (Malay ,Chinese ,Indian ) through Malaysian novels in English: ‘The Rice Mother', ‘Evening Is the Whole Day’, ‘Green Is the Color’, and ‘The Garden of Evening Mist’.